THE INFLUENCE OF TRANSPARENCY, ACCOUNTABILITY, AND MANAGEMENT QUALITY ON INCREASING MUZAKI’S INTEREST - Alfi Wahdatul Ilmi; Abdul Latif Rizqon; Mohammad Zen Nasrudin Fajri; Rusyda Afifah Ahmad (AN NUQUD, 2023)
The implementation of zakat in Indonesian society seems that there is still a gap between hope and reality, the majority of Indonesian Muslims have great zakat potential, but in reality, zakat funds are collected nationally through the National Amil Zakat Agency (BAZNAS) are far from what is expected. The Amil Zakat Nasional Agency (BAZNAS) has future challenges in the management of zakat to improve coordination between the Amil Zakat Agency and zakat institutions in Indonesia. This research aims to find out the Influence of Transparency, Accountability, and Quality of Zakat Management on muzaki interest in the BAZNAS Tasikmalaya Regency. This study uses a quantitative methodology, while the data source in this study is primary data by using questionnaires as a data collection tool. The population in this study is the entire muzaki in BAZNAS Tasikmalaya Regency with a total of 5803 muzaki. The samples in this study used Maximum Likelihood. The sample was taken as many as 140 Muzaki in BAZNAS Tasikmalaya Regency. The sample selection method used is a nonprobability method that is random sampling which is a randomly selected sampling technique from muzaki that has been tapped. Data is processed using SEM analysis with Smart-PLS 3.0 applications. The results of this study are the variables of transparency, accountability and management quality at BAZNAS Tasikmalaya Regency simultaneously affect the increase in interest in muzakki. However, partially accountability has a positive and significant effect on increasing interest in muzakki, and transparency has a positive and significant effect on increasing interest in muzakki, while management quality has a significant negative effect, this is proven to have a significant but negative effect on increasing interest in muzakki. In this study, transparency is a connecting variable between the accountability variable and management quality on the interest of muzaki, so that all variables are said to have a positive and significant influence through the transparency variable